1973
DOI: 10.1113/jphysiol.1973.sp010130
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of dog gastric mucosal blood flow by radioactive aniline clearance compared with amidopyrine clearance

Abstract: SUMMARY1. Methods for the estimation of radioactive aniline in body fluids are described. The recovery of aniline added to blood, plasma and gastric juice was over 90 % of the recovery from saline.2. In the doses used aniline caused methaemoglobinaemia of 5-11 % of total haemoglobin. No other effect was detected. Gastric secretion was also unaffected. 3. Aniline clearance increased in parallel with acid secretion from Heidenhain pouches in conscious dogs and in anaesthetized dogs. In conscious dogs the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Food was withheld for 18 h before experiments, but water was allowed. Mucosal blood flow (MBF) (ml/min) was estimated by clearance of radioactive aniline (Curwain & Holton, 1973), and pouch acid secretion (gmol H+/min) was measured by titration against 0.1 M NaOH with phenolphthalein as indicator. Where appropriate, acid output, MBF and changes in their ratio were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food was withheld for 18 h before experiments, but water was allowed. Mucosal blood flow (MBF) (ml/min) was estimated by clearance of radioactive aniline (Curwain & Holton, 1973), and pouch acid secretion (gmol H+/min) was measured by titration against 0.1 M NaOH with phenolphthalein as indicator. Where appropriate, acid output, MBF and changes in their ratio were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Aspirin 20 mM in Sorensen's phosphate buffer 0.67 M, pH 6.0 formed buffered aspirin. When aspirin was studied without secretory stimulation 80 mm HCI was instilled into the pouch throughout to prevent back-diffusion of aniline (Curwain & Holton, 1973) (1-2 ,ug/ml). Prostaglandins E2 and F2a (50-300 ng/ml) always caused contraction, but lower concentrations were ineffective; prostaglandin FlIa (0.3-3 gg/ml) had no effect or caused contraction.…”
Section: Drug Solutionsmentioning
confidence: 99%
“…Of the other weak bases which satisfy the necessary criteria for use in gastric clearance measurements, aniline is readily available as the 'IC isotope. Moreover, recent studies in the dog have shown that clearance of both aminopyrine and ['4C]-aniline gives similar estimates of MBF (Curwain & Holton, 1971, 1973.…”
Section: Introductionmentioning
confidence: 96%
“…There have been only a few reports of the use of the anaesthetized dog with an acute gastric fistula for the assessment of gastric acid secretion (Black, Fisher & Smith, 1958;Curwain & Holton, 1973). This preparation has the advantage of allowing simultaneous measurement of gastric secretion, cardiovascular and respiratory parameters.…”
Section: Introductionmentioning
confidence: 99%